Correlation and path coefficient analysis of grain yield and Agronomic characters of bread wheat (Triticum aestivum L.) under rainfed conditions - Noori, Shang Haseeb Abdulqader (Sulaimani Journal for Pure and Applied Sciences, 2018)
The following study was done during the winter seasons of 2015-2016 at Qlyasan Agricultural Research Station, College of Agricultural Sciences, University of Sulaimani, using factorial (6×6×4) design conducted in Randomized Completely Block Design (RCBD) with three replicates to study the effect of planting date, plant densities and removal treatments of bread wheat (Adana-99) cultivars to establish the relationship between yield components and plant traits to the yield (output) of the grain. After the collection of data on bread wheat, a correlation analysis and a path analysis were carried out. Positive and highly significant correlation recorded between grain yield and the spike length, spike weight, number of spikelets/spike, number of grains/spike, weight of grains/spike, 1000- grain weight, harvest index and biological yield. Concerning the path coefficient analysis, grain yield represented the (dependent variable) and all characters, were the (independent) ones. Maximum and positive direct effect on grain yield recorded by biological yield was (0.855) and followed by harvest index was (0.337). While number of grains/spike was (-0.045) recorded maximum negative direct effect on grain yield. These relations can be used as selection criteria in breeding studies to improve the higher yields cultivars for that region.
Keywords: Bread wheat; Grain yield; Correlation coefficient and path analysis